Detection of multidrug-resistant (MDR) Staphylococcus aureus and coagulase-negative staphylococci (CoNS) in cow milk and hands of farmers in East Java, Indonesia - ASWIN RAFIF KHAIRULLAH; SHENDY CANADYA KURNIAWAN; SRI AGUS SUDJARWO; MUSTOFA HELMI EFFENDI; DANIAH ASHRI AFNANI; OTTO SAHAT MARTUA SILAEN; GIOVANNI DWI SYAHNI PUTRA; KATTY HENDRIANA PRISCILIA RIWU; AGUS WIDODO; SANCAKA CHASYER RAMANDINIANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Khairullah AR, Kurniawan SC, Sudjarwo SA, Effendi MH, Afnani DA, Silaen OSM, Putra GDS, Riwu KHP, Widodo A, Ramandinianto SC. 2023. Detection of multidrug-resistant  Staphylococcus aureus and coagulase-negative staphylococci in cow milk and hands of farmers in East Java, Indonesia. Biodiversitas 24: 658-664. Cow milk is a nutrient-dense food containing various nutrients, i.e., carbohydrates, fat, and protein. However, it can potentially spread several pathogenic bacteria, such as staphylococci. Staphylococci cause public health problems. Staphylococcal strains were divided into two groups based on coagulase characteristics, namely coagulase-positive and coagulase-negative staphylococci (CoNS). Coagulase-positive was represented by Staphylococcus aureus. S. aureus and CoNS can become resistant to several antibiotics, known as multidrug resistance (MDR) bacteria. S. aureus and CoNS bacteria are known as causal agents in human infections. This study aims to identify the presence of multidrug resistance S. aureus and CoNS bacteria in several dairy farms in East Java, Indonesia. We collected 332 milk and 125 swab samples from the hand of farmers from several dairy farms in Probolinggo, Tulungagung, and Blitar of East Java, Indonesia. The collected S. aureus and CoNS were tested for antibiotic susceptibility using the disc diffusion method. The antibiotic used were cefoxitin, erythromycin, gentamicin, tetracycline, and oxacillin. The results of isolation and identification based on morphological and biochemical characteristics showed that out of 457 samples, 291 samples (63.68%) were positive for S. aureus, and 166 samples (36.32%) were positive for CoNs. There were 15 S. aureus isolates (5.15%) and 7 CoNS isolates (4.22%) confirmed as MDR; therefore, it is confirmed that S. aureus and CoNS resistance to various drugs was very high in the province of East Java. Intensive livestock systems, high livestock densities, and excessive use of antibiotics in modern dairy systems may predispose the developing growth of MDR S. aureus and CoNS infections. In conclusion, the results of this study indicate the presence of very high multidrug resistant S. aureus and CoNS in the East Java provinces. MDR bacteria can be prevented from spreading by improving biosecurity, hygiene in the milking process, and regular health care for animals and dairy workers.